Morphometric Relief Aspects Identification of Khabour River Basin - Jinan Rahman Ibrahim (QALAAI ZANIST JOURNAL, 2021)
Relief Aspects provides data regarding erosion properties of the river basin, such as the morphological properties of the relief, overall slop, and erosion severity. The Khabour River Basin has severe slopes, resulting in high runoff and soil erosion. This creates large latent energy to move water and sediment downward per unit of length. Besides, the ruggedness number of the study area basin is (7.23). The high value indicates that the area is characterized by rugged relief soil erosion and structural complexity. Furthermore, the dissection index (Dis) of the study area which was 0.50, indicates that the basin is still in the youth stage and its reliefs are in constant development instead of morph-metrical Hezel and the sub-Khabour. Hezel River basin has relatively higher values than Al Khabour River main and sub-basin. For example, the slop of the Hezel River basin is (34.73), while the main Khabour Basin (23.7), compared to al- Khabwr sub-Basin (22.60) and the river canal slope (22.1) , while the slope of the sub-Khabour River canal (14.4). The Hezel Basin also has a significant increase in the relief number, relative relief ratio, and ruggedness number. The study area basin is characterized by the modern geomorphology, the activity of water erosion factors, the high proportions of both stripping and transferred materials and basin runoff speed which resulted in a decrease in the percentage of filtered water to the subsurface layers due to the complex nature of the mountain basin, the slop intensity and surface ruggedness.